Correlations of Resource Bricolage and Exaptation With Low-Cost Breakthrough Innovations: Moderating Effect of Organizational Agility - Tang, Chaoyong; Shi, Yongzhi; Cai, Ruilin (Frontiers in Psychology, 2022)
The mechanism influencing resource bricolage driving low-cost breakthrough innovations remains unclear. By introducing exaptation and organizational agility, this study creates a regulated mediation model, explores effects of resource bricolage on low-cost breakthrough innovations, and analyzes the moderating effect of organizational agility and mediation effect of exaptation. The results revealed that resource bricolage exerted a significant positive impact on low-cost breakthrough innovations, and exaptation played a mediation role between resource bricolage and low-cost breakthrough innovations. In addition, both marketing agility and operational agility positively regulated the correlation between resource bricolage and exaptation. Further research revealed that the mediation effect of exaptation was positively regulated by marketing agility and operational agility, respectively. Overall, this study enriches the discussion of the impact mechanism of breakthrough innovations by resource bricolage and provides valuable enlightenment for enterprises to implement innovation-driven development strategies in the context of economic transformation.